الأزمة الاقتصادية العالمية من وجهة نظر الاقتصاد السياسي - الخليل, فادي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يناقش البحث موضوع الأزمة الاقتصادية العالمية الراهنة بالاستناد إلى تحليل خصائص الرأسمالية وبالتحديد خصائص التقلبات الاقتصادية ومراحل الدورة الاقتصادية الرأسمالية، انطلاقاً من فرضية دورية الأزمات الاقتصادية الرأسمالية، والتي تعمقت في ظل النهج الليبرالي المعتمد على الأسواق المالية بعيداً عن الإنتاج السلعي الحقيقي. وبالتالي يحاول الباحث استعراض الجذور الحقيقية للأزمة الاقتصادية العالمية ودراستها وتحليلها للوقوف على حقيقة هذه الأزمة وتداعياتها على الاقتصاد العالمي بشكل عام والاقتصاديات العربية بشكل خاص، واستعراض الآليات الموضوعة لمواجهة هذه الأزمة والآفاق المستقبلية لتطورها. كما يناقش الباحث فكرة احتمال كون هذه الأزمة مصطنعة أم ناتجة عن اختلالات هيكلية في البنيان الاقتصادي الرأسمالي، وصولاً إلى النتائج التي برهنت صحة فرضية البحث بتوضيح السمة الدورية في الأزمات الاقتصادية المتعلقة بطبيعة ونهج الاقتصاد الرأسمالي. The subject of research discusses the current global economic crisis on the basis of analysis of the characteristics of capitalism and particularly, the characteristics of economic fluctuations and the stages of the economic cycle of capitalism, under the assumption of periodic economic crises of capitalism, which has deepened in light of the liberal approach adopted in the financial markets away from the real commodity production. Thus, the researcher tries to review the real causes of the global economic crisis, studied and analyzed to determine the truth of this crisis and its repercussions on the global economy in general and the Arab economies in particular, and review mechanisms provided to address this crisis, and the prospects of its development. The researcher also discusses the possibility that this crisis was fabricated or caused by structural imbalances in the economic structure of the capitalist economic structure, to the results that have demonstrated the validity of the hypothesis of the research to clarify the attribute of periodic economic crises on the nature and approach of the capitalist economy